South African Indians in Natal: The question of belonging, lived histories, and portraits - Sadhai, Pushpaganthie (Department of Sociology, 2024)
This thesis draws on the life histories of eight South African Indian individuals, (six of whom grew up in Natal during the 1960s/1970s and two of whom grew up in the 1930s/1940s), to understand how they lived through, navigated and resisted the apartheid social order. Based on interviews and oral accounts, I create vivid portraits of their lives to discuss survival strategies of materially deprived South African Indian families, and forms of reciprocity and mutuality they lived by in the age of apartheid. Apartheid, for many South African Indian working-class families brought deep deprivation but also petty benefits, and relatively greater opportunities to access education and obtain social mobility. Mindful of that history, I mobilize family and individual portraits to address the so-called “Indian question” and reflect on their sense of belonging in South Africa. As we know, the divide and rule legacy of the colonial state, the grave hardships faced by the majority of South Africans and populist politics of othering, continue to fuel racial tensions between Black South Africans and South African Indians. Against this background, I describe the everyday lives and constructive contributions of South African Indians, to chart a meaningful and ethical mode of living, in the only place they call home. I conclude that, notwithstanding the many contradictions that exist in our 28-year-old democracy, South Africa remains as per the freedom charter, our country (all races), and that we have the power to effect changes in our everyday lives, though small acts of compassion and care—through Ubuntu.